Development and in vitro evaluation of microparticles of fluoxetine in galactomannan against biofilms of S. aureus methicilin resistant. (15th January 2021) - Josino, Maria Aparecida Alexandre; Rocha da Silva, Cecília; de Andrade Neto, João Batista; Barroso, Fátima Daiana Dias; Juvêncio da Silva, Lisandra; Cavalcanti, Bruno Coêlho; de Moraes, Manoel Odorico; Brito, Débora Hellen Almeida; Ricardo, Nágila Maria Pontes Silva; Júnior, Hélio Vitoriano Nobre
Abstract: The emergence of multidrug-resistant (MDR) bacteria is a global problem, by reducing the effectiveness of traditional antibiotics and decreasing the therapeutic arsenal to treat bacterial infections. This has led to an increase in researches about how to overcome this resistance to antibiotics. One strategy is the repositioning (or repurposing) of existing drugs not previously used to combat microorganisms, rather than the development of new drugs. Fluoxetine (FLX) is a selective serotonin reuptake inhibitor (SSRIs) and is considered one of the first highly selective antidepressants of the monoamine neurotransmitter serotonin (5-HT). The objective of this study is to prepare and physically characterize fluoxetine microparticles with galactomannan and evaluate their efficacy against strains of Staphylococcus aureus sensitive and resistant to methicillin. The microparticles were analyzed by differential scanning calorimetry (DSC), infrared analysis (IR) and X-ray diffraction (XRD). In addition, the percentage of encapsulation efficiency (EE%) and drug release kinetics were determined in vitro, along with the determination of the minimum inhibitory concentration (MIC) and evaluation of the action against biofilms. Physical tests were conducted to characterize galactomannan (GAL), FLX, oxacillin (OXA) and the galactomannan/fluoxetine microparticles (GFM). The EE% value was 98 % and, in regard the release, tests with the microparticles released about 60 % of the drug in 200 min. The isolated MIC results for FLX (255 μg/mL) and OXA MIC (1.97–15.62 μg/mL) showed that the strains were resistant. Furthermore, in the biofilms, microparticles showed statically significant improvement for all concentrations used. The study revealed that fluoxetine encapsulated in microparticles has the potential to act as an effective antimicrobial agent.